Association of systemic immune-inflammation index with all-cause and cardiovascular mortality among adults with depression: evidence from NHANES 2005–2018 - Xinping Yu; Heqing Zheng; Mingxu Liu; Lanxiang Wu; Sheng Tian; Wei Wu (BMC Psychiatry)
Abstract Background The relationship between the systemic immune-inflammatory index (SII) and the mortality of adults with depression is uncertain. Methods This study included adults with depression who were surveyed in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. Cox proportional hazards regression models to compute hazard ratios (HR) and 95% confidence intervals (CI) for mortality.The restricted cubic spline(RCS), Kaplan-Meier curve analysis, time-dependent ROC analysis, subgroup and sensitivity analyses were also used. Results A total of 2442 adults with depression were included in the final analysis(average age: 46.51 ± 0.44 years). During a median follow-up of 89 months, there were 302 all-cause deaths and 74 cardiovascular deaths. The fully adjusted model showed that an increment of 100 unit in SII corresponded to an increased HR of 1.05(95% CI,1.02,1.08, p = 0.003) for all-cause mortality and 1.06(95% CI,1.02,1.10, p = 0.004) for cardiovascular mortality, respectively. The RCS analysis indicated a J-shape relationship between SII and all-cause mortality and a positive linear association between SII and cardiovascular mortality.The time-dependent ROC analysis exhibited excellent efficacy in SII for predicting all-cause and cardiovascular mortality at 1, 3, 5 and 10 years. Conclusions Higher SII levels were associated with increased risk of all-cause and cardiovascular mortality in adults with depression. Clinical trial number Not applicable.